Mark Twain & the Bible - Ensor, Allison (Lexington : University Press of Kentucky, 2015)
Mark Twain enthusiasts will welcome this study of the great writer's attitude toward the Bible -- and of the influence of Holy Writ upon both the man and the artist. While the theological beliefs of Twain have been well documented, Mr. Ensor's study is the first to consider only his familiarity with the Bible and the extensive use of it in his writings. The Bible elicited by turns pious, skeptical, comical, and even hostile reactions in Twain, but he could not ignore it. Mr. Ensor examines manifestations of these conflicting impulses from the early newspaper articles to the autobiographical dic.
Cover; Title; Copyright; Acknowledgments; Contents; 1. The Writer & The Bible; 2. To The Holy Land; 3. Three Biblical Images; 4. The Attack On The Bible; 5. Conclusion; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W.
Includes bibliographical references and index.
Print version record.
Keywords: Bible -- In literature; Christian fiction, American -- History and criticism; Twain, Mark, 1835-1910 -- Religion; HUMOR -- General; Twain, Mark, -- 1835-1910 -- Religion; Christian fiction, American -- History and criticism; Bible -- In literature; HUMOR / General; Electronic books